Optimization of process condition for extraction of gelatin from red tilapia skin (Oreochromis niloticus) by High Pressure Processing (HPP) - Yusof, N.; Jaswir, Irwandi; Jamal, Parveen; Jami, Mohammed Saedi; Octavianti, Fitri (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Extraction of gelatin using traditional acid-base pretreatment method has several limitations such as time consuming and causes serious water pollution. Chemical treatment often being used as an alternative process to overcome the weaknesses of the conventional method. However, excessive chemical elements would damage the structure of the gelatin due to its high sensitivity to the acid content. High Pressure Processing (HPP) is a novel and environmental friendly method that has been suggested to assist gelatin extraction. Pressurization during pretreatment could reduce the extraction time and amount of acid used. It also has a potential in enhancing the properties of the gelatin extract and increasing the gelatin yield. In this research, One-Factorat-Time (OFAT) and optimization study were done to determine the optimum parameters for extraction of gelatin assisted by HPP from red tilapia skin. Four parameters; applied pressure, pressure holding time, ratio of acid to skin and extraction time have been selected for the OFAT design and concentration of the gelatin extract and percentage of yield gelatin were evaluated. From OFAT, optimum technical parameters for response surface optimization design were 250 MPa pressure, 7.5 ml of acid to 1 g of skin and 12 hours extraction time. Pressure holding time was fixed for 10 min. FCCCD has been used for optimization study. Results from the data shows that the optimum conditions for gelatin extraction from red tilapia skin were 250 MPa for pressure, 10 min of pressure holding time, 7.5 ml of acid for 1 g of skin and 12 hours of extraction time while the maximum concentration and yield were 19.51 mg/ml and 32.04% (320.4 mg/g), respectively. These findings proved that HPP could increase the concentration and the yield of the gelatin while reducing the chemical waste and shortening the extraction process.